Incorporating Land Tenure Security into Conservation. Issue 2 (28th June 2017) - Robinson, Brian E.; Masuda, Yuta J.; Kelly, Allison; Holland, Margaret B.; Bedford, Charles; Childress, Malcolm; Fletschner, Diana; Game, Edward T.; Ginsburg, Chloe; Hilhorst, Thea; Lawry, Steven; Miteva, Daniela A.; et al.
Abstract: Insecure land tenure plagues many developing and tropical regions, often where conservation concerns are highest. Conservation organizations have long focused on protected areas as tenure interventions, but are now thinking more comprehensively about whether and how to incorporate other land tenure strategies into their work, and how to more soundly ground such interventions on evidence of both conservation and human benefits. Through a review of the literature on land tenure security as it relates to conservation practice, predominantly in the tropics, we aim to help conservation practitioners consider and incorporate more appropriate land tenure security interventions into conservation strategies. We present a framework that identifies three common ways in which land tenure security can impact human and conservation outcomes, and suggest practical ways to distill tenure and tenure security issues for a given location. We conclude with steps for considering tenure security issues in the context of conservation projects and identify areas for future research.